Corruption and turnout in Portugal - a municipal level study - Stockemer, D.; Calca, P. (Crime, Law and Social Change, 2013)
This article ventures to be one of the first studies that examines the relationship between corruption and electoral turnout on the sub-national level. Taking Portugal, a southern European country with nationally relatively high levels of corruption and relatively low levels of turnout, as a case, we examine the relationship between the two concepts across Portugal's 304 out of 308 municipalities for the legislative elections in 2005 and 2009. Controlling for municipal level GDP per capita, unemployment, the percentage of senior citizens, and population density, as well as the closeness of the election and the district magnitude, we find corruption to be a rather strong mobilizing agent. Compared to "clean" municipalities, our results indicate that turnout is several percentage points higher in "very corrupt" municipalities.